PENGARUH ISOLAT HERBA VERNONIA CINEREA TERHADAP SPERMATOGENESIS TIKUS PUTIH - Gupta Widotama, I G. B. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008)
The influence of Vernonia cinerea Less. on spermatogenesis of rat has been investigated. This research was held into two steps. The first activity was isolation and purification of the herb of. V. cinerea Less.. The purity of isolate was showed by the appearance of only one spot on chromatogram and its physical characteristic. The second step was identification the spermatogenesis using three groups of rat for 49 days namely i.e. normal group that was administered by normal saline, group I that is administered by 0.05 mg/g body weight of V. cinerea Less. isolate i.p., and group II that was administered by 0.025 mg/g B.W of V. cinerea Less. isolate i.p. Histological preparat with PAS- Hematoxylin dyeing was used in tubulus seminiferus observation. The result showed the cocci form of tubulus seminiferus and basalis membrane appearance. This concluded that the isolate of V. cinerea Less. herbs influenced the spermatogenesis of rat.
Keywords: Spermatogenesis, Vernonia cinerea Less., tubulus seminiferus